Self-Assembly of TiO2/CdS Mesoporous Microspheres with Enhanced Photocatalytic Activity via Hydrothermal Method - Sujing Yu; Juncheng Hu; Jinlin Li (International Journal of Photoenergy)
Self assembly of TiO2/CdS mesoporous microspheres was synthesized via hydrothermal method. The samples were characterized by X-ray powder diffraction (XRD), ultraviolet-visible diffuse reflectance spectroscopy (DRS), transmission electron microscopy (TEM), energy-dispersive spectroscopy analysis (EDS), high-resolution transmission electron microscopy (HRTEM), Brunauer-Emmett-Teller (BET), X-ray photoelectron spectroscopy (XPS), and photoluminescence spectra (PL). The as-synthesized TiO2/CdS mesoporous microspheres showed superior photocatalytic activity for the degradation of RhB under either visible light or simulated sunlight irradiation; the 10 wt% TiO2/CdS sample showed the best performance. Moreover, this catalyst showed improved stability, and the activity did not decrease significantly after four recycles. The heterojunction between TiO2 and CdS may be favorable for the transport of photoinduced electrons from CdS to TiO2. In addition, the mesoporous structure could increase the utilization of light energy and facilitate the diffusion of reactants and products during the photocatalytic reaction.